Huangqi Shengmai Yin Protects against Radiation-Induced Cardiac Fibrosis Injury by Regulating the TGF-β1/Smads and MMPs. (13th May 2019) - Gu, Jing; Liu, Yongqi; Wu, Hongyan; Li, Hailong; Liu, Kai
Abstract : Background . Radiation-induced heart damage is considered to be a progressive process of fibrosis. Emerging evidence has indicated that the Smads and matrix metalloproteinases (MMPs)/tissue inhibitors of MMPs (TIMP) may be involved in radiation-induced cardiac fibrosis (RICF) by regulating the activation of TGF- β 1 signaling pathway. Based on this, the present study was undertaken to characterize the effect of Huangqi Shengmai Yin (HSY) on RICF in a rat model. Methods . Precardiac region of rats was irradiated with 25 Gy X-rays, and their myocardial pathology scores in terms of injury and collagen volume fraction (CVF) and the expression levels of fibrotic molecules were detected. Results . The pathology scores and CVF in myocardial tissue increased after irradiation, and the expression of TGF- β 1, Col1, and Col3 increased. This change indicated that such irradiation promoted the fibrosis damage in rat hearts. The damage was accompanied by an increase in the expression of Smad 2, Smad3, Smad4, and MMP14 and a decrease in the expression of Smad 7 and TIMP1. Administration of HSY weakened the RICF by decreasing pathology score and CVF and decreased the expression of TGF- β 1, Col1, and Col3 in irradiated rat hearts. In addition, Smad2, Smad3, Smad4, and MMP14 were downregulated, while Smad 7 and TIMP1 were upregulated during intervention with HSY. Conclusions . The involvement of the TGF- β 1/Smads and MMPs/TIMP system in RICF was confirmed. This study demonstrated, for the first time, that HSY attenuates the effects of RICF in a rat model. The effect HSY was found to be closely related to the TGF- β 1 /Smads signaling pathway and MMPs system. These results suggest that HSY is a prospective drug for clinical treatment of RICF.